2019
DOI: 10.3389/fncel.2019.00241
|View full text |Cite
|
Sign up to set email alerts
|

Selective Neural Deletion of the Atg7 Gene Reduces Irradiation-Induced Cerebellar White Matter Injury in the Juvenile Mouse Brain by Ameliorating Oligodendrocyte Progenitor Cell Loss

Abstract: Radiotherapy is an effective tool for treating brain tumors, but irradiation-induced toxicity to the normal brain tissue remains a major problem. Here, we investigated if selective neural autophagy related gene 7 ( Atg7 ) deletion has a persistent effect on irradiation-induced juvenile mouse brain injury. Ten-day-old Atg7 knockout under a nestin promoter (KO) mice and wild-type (WT) littermates were subjected to a single dose of 6 Gy whole-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…In our previous studies, we demonstrated that selective Atg7 deletion prevents irradiation-induced caspase-3 activation, microglia activation, and in ammation and reduces irradiation-induced neural stem and progenitor cell death during the acute injury phase [8]. We also showed that selective inhibition of autophagy in neural cells reduces irradiation-induced subacute cerebellar white matter injury by decreasing OPC loss [7]. However, the mechanism through which autophagy de ciency prevents white matter injury after irradiation in the subacute injury phase is still unclear, and further research is needed.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In our previous studies, we demonstrated that selective Atg7 deletion prevents irradiation-induced caspase-3 activation, microglia activation, and in ammation and reduces irradiation-induced neural stem and progenitor cell death during the acute injury phase [8]. We also showed that selective inhibition of autophagy in neural cells reduces irradiation-induced subacute cerebellar white matter injury by decreasing OPC loss [7]. However, the mechanism through which autophagy de ciency prevents white matter injury after irradiation in the subacute injury phase is still unclear, and further research is needed.…”
Section: Discussionmentioning
confidence: 88%
“…Floxed Atg7 mice were characterized as previously described [6,7] and were crossed with a nestin-Credriven line to produce Atg7 ox/ ox; Nes−Cre knockout (Atg7 KO) and Atg7 ox/+; Nes−Cre mice (WT). All of the mice were housed in a temperature-controlled and pathogen-free environment with a 12:12-hour light-dark cycle.…”
Section: Animals and Ethical Permissionmentioning
confidence: 99%
See 3 more Smart Citations